Armed forces and society. Sociological essays. Ed. by J.[A.A.] van Doorn. [With contribs. of M.D. Feld, B. Abrahamsson, C.B. Otley, a.o. With pref. by M. Janowitz] (Mouton, 1968)
With indices and tabs.